Availability and Utilization of Health Care Services and the Health-Related Quality of Life of Older Adults in Greater Accra - Eliason, C. (University Of Ghana, 2018)
Background Although ageing is a desired phenomenon, it is associated with health-related challenges which affect the quality of life of older adults. These increase the demand for health care services as a growing number of older people are living with chronic diseases and disabilities. This study assessed the availability and utilization of health care services and the health-related quality of life of older adults living in Greater Accra region in Ghana. Methods It was a cross-sectional study using quantitative and qualitative approaches. The survey involved a total of 500 older adults aged 60 years and above, residing within the catchment areas of six selected health facilities in Greater Accra and assessed the factors influencing utilization, health-seeking behaviour, and health-related quality of life. The qualitative aspect explored the availability of health care services for older persons through key informant interviews with eleven curative and preventive health professionals working in the s ix selected health facilities. Thematic content analysis was employed in the qualitative data analysis. The survey utilized an integrated questionnaire that included health care utilization, health-seeking, and SF-36 Health survey for health-related quality of life among community-dwelling older adults. Descriptive, bivariate and multivariate logistic regression analyses were employed to examine the associations between population characteristics, use of health care services, health-seeking behaviour and health-related quality of life. Results Four major themes emerged from the key informant interviews that included; accessibility of services, availability of special services for older persons, affordability of health services and knowledge of policy for care of older persons. Dedicated services for older adults did not exist. However, some general curative and preventive services were available in the existing formal health system. Also, knowledge of the existence of a policy framework for older persons was inadequate among health workers. Utilization of healthcare was good (65%) among older adults. Determinants of utilization were age, residential status, source of income, employment, benefit from government, health status rating and diagnosed with chronic disease. Majority of the respondents (89%) intended to seek treatment from the hospital and did so when they fell sick. Employment status of the older person influenced their health-seeking behaviour. The overall health-related quality of life was good (mean score 57.5) despite the low physical health component score (43.8). The predictors of overall health-related quality of life were marital status, a rating of current health status, diagnosed with chronic disease and utilization of health care service. Conclusion Dedicated health care services for older adults were not available in the formal health system. Utilization of health care services was good. Majority of older adults sought health care from hospitals when they fell ill. Overall health-related quality of life was good, but the physical health functioning was limited. Population characteristics and utilization of health care services were significantly associated with health-related quality of life but health seeking behaviour was not. This study recommends that a dedicated service for the older adults need to be instituted. This may provide the basis for health management of older persons and will also help the central and local government to devise appropriate health intervention strategies to improve and promote the health-related quality of life of older persons. Key words: Older adults, health care service utilization, health seeking behaviour and health related quality of life
PhD.
Keywords: Health Care Services; Older Adults; Greater Accra; Health-Related Quality of Life